SYNCHRONIZATION OF TERRESTRIAL PROCESSES WITH FREQUENCIES OF THE EARTH-MOON-SUN SYSTEM - Sidorenkov, N. S. (Одеські астрономічні публікації, 2016)
It is established that the frequencies of the quasi-biennial oscillation (QBO) of atmospheric winds and the Chandler wobble (CW) of the Earth's poles are synchronized with each other and with the fundamental frequencies of the Earth–Moon–Sun system. The QBO and CW frequencies are resonance combinations of the frequencies of the Earth–Moon system's yearly rotation around the Sun, precessions of the lunar orbit, and the motion of its perigee. The QBO and CW frequencies are in a ratio of 1:2. The synchronizations between Mul'tanovskii's natural synoptic periods and tidal oscillations of the Earth's daily rotation rate, as well as between variations in climatic characteristics and long-time fluctuations of the Earth's rotation rate are described.